(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was conducted to determine the sero-prevalence of canine visceral leishmaniasis (VL) among street and owned dogs at Trishal Upazila of Mymensingh district, Bangladesh. Material and methods: Blood was collected asceptically from targeted dogs and serum was separated out using standard centrifugation method. The rK39-antigen-based dipstick test was used to detect anti-leishmania antibodies in serum. Results: The study revealed that 35% of the dogs in the study area were sero-positive for L. donovani. Living status of the dogs (street or owned) was a potential risk factor and sero-prevalence was significantly higher in free roaming street dogs (P=0.009) and dogs with skin lesions and enlarged lymph nodes (P<0.05). The female and adult dogs were more susceptible. Conclusion: VL is an important zoonotic disease wich is transmissible to humans by the bite of phlebotomine sand fly. Dogs are the main reservoir. The higher sero-prevalence of VL indicates the potential rule of dogs to maintain the zoonosis wich need to be explored more specifically by isolation and typing of the parasite. http://doi.org/10.5455/javar.2017.d217